Redevelopment and examination of the psychometric properties of school physical activity environment in Chinese - Ka-Man Leung (BMC Public Health)
Abstract Background This study adapted the Questionnaire Assessing School Physical Activity Environment (Q-SPACE) into Chinese and evaluated its psychometric properties. Methods A total of 253 primary school and 267 secondary school students completed the modified Q-SPACE-Chi twice, with a 2-week interval, between November 2022 and March 2023. A confirmatory factor analysis and the assessment of measurement invariance supported the efficiency of the three-factor Q-SPACE-Chi (i.e., physical environment, social environment, and school policy) across various groups. Results The results confirmed the factorial validity of the three-factor modified A-SPACE-Chi, with all items demonstrating significant loadings in the physical environment, special environment, and social policy dimensions. The predictive validity results revealed significant associations between student’s perceived school physical activity environment and the physical activity level. Moreover, the test-retest reliability and internal consistency of the adapted questionnaire were moderately favorable. Conclusion This modified Q-SPACE-Chi, with element of school policy therefore presents an additional valuable tool for researchers or practitioners aiming to evaluate how Chinese students perceive the school physical activity environments within their schools while the measurement properties of Q-SPACE-Chi was invariant among primary and secondary students.